High deposition rate wire based additive manufacture of Ti-6Al-4V. - Wang, Chong (Cranfield University, 2020)
Wire + arc additive manufacture (WAAM) is characterised by high deposition rate, short lead-time and relatively low cost, making it suitable for building large-scale metal components. In practical production, high deposition rates are required to reduce the lead-time and overall costs of the components. However, there is a trade-off between the productivity and quality of the deposited components. This is because the fundamental building block of each part, the shape of each individually deposited bead, is dictated by the melt pool dynamics, which is more challenging to control at high heat inputs with any single axisymmetric heat source. Therefore, this thesis undertakes a study of a novel wire based additive manufacture (AM) process, which combines a plasma transferred arc (PTA) and a laser heat sources, aiming to achieve high deposition rates and near-net shape. First, the limitations of a single PTA deposition process, in terms of the deposition rate and process tolerance were obtained. It was found that the deposition rate can be improved by changing the energy distribution between the wire and the workpiece. This can be done by increasing the wire diameter or changing the position of the wire with respect to the arc column. To enable a further increase of energy input and deposition rate but without increasing the likelihood of keyhole defects formation, a novel configuration of the PTA process with the vertical wire and inclined torch was examined. Although this process is not omnidirectional, it could reduce the likelihood of keyhole formation. The interaction between the PTA and laser was studied using a finite element (FE) model. This model could predict thermal conditions, such as melt pool geometry, for different process parameters. A wire based PTA-laser hybrid AM process was developed, and the possibility of independent control of deposition rate and bead shape was studied. It has been demonstrated that near-net-shape parts at high deposition rates could be achieved with the PTA-laser hybrid AM. In addition, with the PTA to melt the wire and the laser to control the melt pool size, the deposition rate and bead shape could be controlled independently in the hybrid process. This was then extended to a multi-energy source (MES) approach with two lasers and a PTA. Despite the increased complexity of such a process, it is easier to control the bead dimensions and thermal cycle independently.
Ding, Jialuo - Associate Supervisor
Keywords: Wire + arc additive manufacture (WAAM); plasma arc-laser hybrid additive manufacture; metal transfer; keyhole; melting efficiency; bead shape control; finite element model; multi-energy source